[Laiškas] / Bogdanovičius (Bogdanowicz) Leonas, "Nowiny Wileńskie" redaktorius - Tadui Vrublevskiui. - (:unkn) unknown (My University, 1905)
1 laiškas apie siunčiamą kunigo Milkovskio prospektą "Protest".
Keywords: Rankraščiai; Autografų kolekcija; Laiškai; Vrublevskis, Tadas Stanislovas, 1858-1925; Bogdanovičius (Bogdanowicz), Leonas